T-DepExp: Simulating transitive dependence based coalition formation - Lau, B.; Singh, A.; Tan, Terence Peng Lian (Universiti Putra Malaysia, Universiti Pertanian Malaysia Press, 2015)
In this paper, we introduce T-DepExp system to simulate the transitive dependence based coalition formation (CF). It is a multi-agent based simulation (MABS) tool that aims to enhance cooperation between agents through transitive dependence. Previously, the transitive dependence was introduced by An and his colleagues for expressing the indirect dependence between agents in their cooperation. However, it did not receive much attention. Although it has a few problems need to be addressed, we try to propose our own mechanism to increase the efficiency of the transitive dependence based CF. To simulate MAS dependence relationship, we have included two fundamental dependence relationships in this MABS tool, which are AND-Dependence and OR-Dependence. In addition, the architecture of the T-DepExp system is presented and discussed. It allows possible integration of other features such as budget mechanism and trust model. Subsequently, hypothesis for the experiments and experimental setup are explained. The overall system will be demonstrated for its functionality and the experimental results will also be discussed.